Role of microbial diversity in controlling greenhouse gas emissions from conserved forages - Mahmood, Maheen (Kansas State University, 2021)
Forages are plant materials utilized by grazing livestock. Forages are preserved to provide year-round availability of nutritious feed for livestock and typically conserved as hay (20% moisture content) or silage/haylage/baleage (40-70% moisture content). Silage undergoes natural fermentation process and anaerobic condition is the first and foremost requirement for the process. Under anaerobic condition, conserved forages may serve as an ideal habitat not only for fermenters but also for other diverse microbial groups such as methanogens and denitrifiers, which are involved in the production and reduction of greenhouse gases (GHGs), i.e., methane (CH₄) and nitrous oxide (N₂O). A laboratory study was conducted to examine the GHG production from alfalfa in the absence of oxygen (O₂). The results showed that 2.2 [mu]mol of CH₄ per g-[subscript forage] and 13.0 [mu]mol of N₂O per g-forage were produced, which corresponds to 122.2 and 8,581.2 [mu]g CO₂ eq per g-[subscript forage]., respectively. Based on the annual silage production volume reported by USDA, the N₂O emission potential from forage conservation process was estimated to be 0.3 million metric tons CO₂ equivalent per year, which ranks forage conservation as the third most important yet unaccounted source of N₂O emissions in the agricultural sector. In order to further validate the presence of these microorganisms in forages, PCR amplification was performed using primers targeting microbial genes of interest, especially those associated with denitrification and methane cycle in addition to bacterial 16S rRNA gene. PCR amplification results validated the presence of functional genetic markers for methanotrophs and denitrifiers. The gene marker for methanotrophs (pmoA) was detected prior to the incubation and on the outside of the haybales post two months incubation but disappeared from the inside. The detection of methanogens on the inside of haybale sample after two months of incubation suggested a microbial community shift inside the haybales. The second objective of this study was targeted towards optimizing the protocol for the extraction of microbial DNA from silages as it was hypothesized that different DNA extraction protocols would result in different microbial DNA to total (microbial + plant) DNA ratio. Hence, we employed mechanical and enzymatic cell lysis procedures.
Keywords: Forages; Greenhouse gases; Microbial diversity